Perlawanan dan Kepasrahan: Pandemi Covid-19 di Mata Empat Penyair Arab - Muhammad Luthfi Zuhdi (Center of Language and Cultural Studies, 2020)
The spread of the COVID-19 pandemic which has touched almost all countries in the world has become an important record in human history. The existence of the coronavirus makes countries in the world respond in different ways. Some countries choose to close the space for human movement, while some other countries give freedom to their citizens to carry out activities as usual. The COVID-19 pandemic has also made humans reflect deeply on the situation they are experiencing, including the poets in Arab countries. This article discusses several poems that reflect people's attitudes towards the outbreak. This study discusses 4 poems from four poets who came from Palestine, Egypt, the United Arab Emirates, and Syria. This study uses a qualitative method. The social reflections on the Covid-19 Pandemic that appeared in the four poems were analyzed using the sociological literary theory approach and the Sufism approach. The results obtained from this study indicate that Arab societies have different ways of dealing with pandemics. In a situation of helplessness in facing the Covid-19 pandemic, submission or tawakkal to God Almighty, Mighty is expressed in different languages, even containing elements of resistance